Remyelination varies between and within lesions in multiple sclerosis following bexarotene - Brown, J. William L.; Prados, Ferran; Altmann, Daniel R.; Kanber, Baris; Stutters, Jonathan; Cunniffe, Nick G.; Jones, Joanne L.; Georgieva, Zoya G.; Needham, Edward J.; Daruwalla, Cyrus; Wheeler‐Kingshott, Claudia Gandini; Connick, Peter; et al. (Annals of clinical and translational neurology, 2022)
Objective In multiple sclerosis chronic demyelination is associated with axonal loss, and ultimately contributes to irreversible progressive disability. Enhancing remyelination may slow, or even reverse, disability. We recently trialled bexarotene versus placebo in 49 people with multiple sclerosis. While the primary MRI outcome was negative, there was converging neurophysiological and MRI evidence of efficacy. Multiple factors influence lesion remyelination. In this study we undertook a systematic exploratory analysis to determine whether treatment response – measured by change in magnetisation transfer ratio – is influenced by location (tissue type and proximity to CSF) or the degree of abnormality (using baseline magnetisation transfer ratio and T1 values). Methods We examined treatment effects at the whole lesion level, the lesion component level (core, rim and perilesional tissues) and at the individual lesion voxel level. Results At the whole lesion level, significant treatment effects were seen in GM but not WM lesions. Voxel‐level analyses detected significant treatment effects in WM lesion voxels with the lowest baseline MTR, and uncovered gradients of treatment effect in both WM and CGM lesional voxels, suggesting that treatment effects were lower near CSF spaces. Finally, larger treatment effects were seen in the outer and surrounding components of GM lesions compared to inner cores. Interpretation Remyelination varies markedly within and between lesions. The greater remyelinating effect in GM lesions is congruent with neuropathological observations. For future remyelination trials, whole GM lesion measures require less complex post‐processing compared to WM lesions (which require voxel level analyses) and markedly reduce sample sizes.